2023
DOI: 10.1097/mcc.0000000000001074
|View full text |Cite
|
Sign up to set email alerts
|

Severe infections caused by difficult-to-treat Gram-negative bacteria

Silvia Dettori,
Federica Portunato,
Antonio Vena
et al.

Abstract: Purpose of review Antimicrobial resistance (AMR) in Gram-negative bacteria (GNB) poses a significant global health concern, contributing to increased infections, mortality rates, and healthcare costs. This review discusses the main clinical manifestations, therapeutic options, and recent findings in managing antibiotic-resistant GNB, with a focus on difficult-to-treat infections. Recent findings Difficult-to-treat resistance (DTR) is a novel classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…Patients' demographic characteristics are summarized in Table 1. Overall, patients with sepsis had a median age of 11 months [4-55 months] and a PRISM III score 24 h after admission of 7 [3][4][5][6][7][8][9][10][11][12]. One hundred and forty-one (32.6%) patients had received antibiotic treatment in the 48 h prior to PICU admission.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' demographic characteristics are summarized in Table 1. Overall, patients with sepsis had a median age of 11 months [4-55 months] and a PRISM III score 24 h after admission of 7 [3][4][5][6][7][8][9][10][11][12]. One hundred and forty-one (32.6%) patients had received antibiotic treatment in the 48 h prior to PICU admission.…”
Section: Study Populationmentioning
confidence: 99%
“…Currently, antimicrobial resistance in Gram-negative bacteria is a growing threat in Europe and worldwide [2,3]. The ability of these bacteria to acquire and modify new genetic material that confers on them new resistance mechanisms is a cause of great concern, especially in children, because of the more limited availability of antimicrobials in pediatric patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…As AMR problem worsens, there is a lack of ideal medications for otitis media treatment, and severe cases may result in hearing impairment. [6][7][8][9] To tackle this, researchers have been striving to develop novel antibiotic alternatives, such as zinc oxide nanoparticles (ZnO NPs), titanium dioxide nanoparticles (TiO 2 NPs), and antimicrobial peptides (AMPs). Each of these drugs has its own strengths in antibacterial properties, yet they also come with their own limitations.…”
Section: Introductionmentioning
confidence: 99%
“…With the widespread use of broad-spectrum antibiotics, the incidence of infections with multidrug-resistant gram-negative bacilli has increased ( Cillóniz et al., 2019 ), significantly worsening the survival rate of infected patients. Gram-negative bacilli infections have become a major challenge to global public health ( Kanj et al., 2022 ; Dettori et al., 2023 ). Studies have shown that the mortality rate of gram-negative bacillary pneumonia is 14.5%-32% ( Feng et al., 2019 ; Kofteridis et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%